Miejsce i rola kobiety w rodzinie na przestrzeni wieków. Od Antyku po I wojnę światową. Zarys problematyki - Kamprowski, Rafał (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
For a long time, history of women was not in the mainstream of interest. The interest for this topic was not shown untill the twentieth century. The aim of this paper is to present a long and difficult struggle to gain the status similar to the one women have nowadays. It is difficult to understand the present reality without going back to the past. The role of women is undergoing a lot of changes all the time. This subject is a huge field for research. The article attempts to give a summary of publications which deal with women’s issues.